Morphology of Three Terra Rossa Soils in East Mediterranean Region, Turkey¶ - Irmak, S.; Aydemir, S. (Asian Journal of Chemistry, 2010)
Morphological and chemical characteristics of three Terra Rossa soils on the Tourous Mountains in the East Mediterranean Region were studied to understand the genesis of Terra Rossa soils. All three soil profiles developed on the CaCO3 rocks. Parent material and climate have affected the morphology and chemistry of soils. The most pedogenic processes are clay accumulation and leaching of carbonates. The low CaCO3 contents can be attributed to the leaching of CaCO3. The leaching of CaCO3 from the profile were caused the red colour Bt horizon. Evidence of alluvial clay occurred as clay films on ped faces in all soil profiles. Argillic horizon have developed result of clay accumulation. The high total contents of Al2O3 and Fe2O3 of soils may be attributed to chemical composition of CaCO3 parent rock. Soil pedons were classified as Typic Rhodoxeralf and Lithic Rhodoxeralf according to the soil taxonomy and chromic luvisol group to the FAO/UNESCO World Soil Map Legend.